New Books: An Annotated Listing. - Bhaskar, K. N.; Finnerty, John; Masulis, Ronald W.; McMickle, Peter L.; Montazemi, A. R.; Perlman, Baron; Reid, Jean Margo; Shapiro, Alan C.; Shepard, Glenn G. (The Accounting Review, 1989)
Abstract This article presents information on various books related to accountancy. The book "An Accountant's Guide to Databases," by K.N. Bhasker, examines the basic concepts and terminology of database management and its implications for the field of accounting. The book begins with a brief introduction to current micro-technology and the organization of computer files and defines three distinctive meanings of the term database relevant to its use in accounting. The purpose of the book "Comprehensive Auditing in Canada: Theory and Practice," by James Cutt, is the development of a theory and methodology for a comprehensive auditing model by examination of current theory and practice in the areas of auditing and policy analysis or program evaluation. The theory and methodology developed is designed primarily for the nonprofit component of the public sector but is extended to the profit component of the public and private sectors. In the book "The British Accounting Review Research Register 1988," edited by K.P. Gee and R.H. Gray, the data presented has been gathered from across 90 universities, polytechnics and colleges, and provides information on 1,072 accounting and finance academic staff members throughout the British Isles.